2008 2nd Electronics Systemintegration Technology Conference 2008
DOI: 10.1109/estc.2008.4684473
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature sintering mechanism of Ag nanoparticle paste

Abstract: Recently, the authors have developed a novel room temperature wiring method with Ag nanoparticle paste. In the present work, the sintering mechanism of Ag nanoparticle paste was clarified through analysis of the adsorption stability and the removal of the dispersant from the Ag nanoparticles. The Ag nanoparticles in the paste are protected by dodecylamine as a dispersant. This paste possesses a substantially long shelf life. When a printed line of Ag nanoparticle paste is dipped in a methanol bath, the methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Silver has an array of properties that can be tuned or enhanced through the control of nanoscale size and morphology for a variety of applications. The field of nanowelding exploits the different thermal behaviors of nanosized particles compared to bulk materials, , which enables the formation of conductive metallic junctions at low temperature. This is of high interest for the fabrication of electronic devices on flexible substrates and for power semiconductor devices. , It remains a challenge to produce junctions with excellent mechanical, thermal, and electrical properties after sintering at temperatures below 200 °C. The sintering process of nanoparticles is highly dependent on their surface characteristics. ,,, Many groups have examined the effects of size and surface coating sinter bonding using spherical nanoparticles. It is now well-established that small silver nanoparticles undergo a rearrangement at temperatures well below their bulk melting point ( T m = 962 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Silver has an array of properties that can be tuned or enhanced through the control of nanoscale size and morphology for a variety of applications. The field of nanowelding exploits the different thermal behaviors of nanosized particles compared to bulk materials, , which enables the formation of conductive metallic junctions at low temperature. This is of high interest for the fabrication of electronic devices on flexible substrates and for power semiconductor devices. , It remains a challenge to produce junctions with excellent mechanical, thermal, and electrical properties after sintering at temperatures below 200 °C. The sintering process of nanoparticles is highly dependent on their surface characteristics. ,,, Many groups have examined the effects of size and surface coating sinter bonding using spherical nanoparticles. It is now well-established that small silver nanoparticles undergo a rearrangement at temperatures well below their bulk melting point ( T m = 962 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al (1999) observed apparently sintered contacts of ~50nm diameter between Ag nanoparticles in an iCA, and similar contacts have been observed between micron-scaled ICA particles (Li and Morris, unpublished data, 1994). Sintering is clearly the key to the lower ICA resistivities appearing in the literature, and may explain the results of Yang et al (2008) by a 'room temperature sintering' process (Wakuda et al, 2008) of enhanced surface diffusion following removal of the protective surface layer.…”
Section: 5mentioning
confidence: 87%
“…Contact resistance reliability problems (Li et al, 1995;Liu et al, 1996;Botter et al, 1998) are primarily due to galvanic corrosion between dissimilar metals at the interfaces (Lu et al, 1999a,b; in the presence of water, with the resulting oxide leading to micro-crack failure (Kim et al, 2008). The resistance drift can be reduced or slowed by the addition of corrosion inhibitors, oxygen scavengers, and/or sacrificial anode material to the polymer matrix Wong, 1999a, 2000e;Takezawa et al, 2002), and moisture can be minimized with anhydridecured epoxies (Lu and Wong, 2000d).…”
Section: Galvanic Corrosionmentioning
confidence: 98%
“…Transposed to sintering, this model allows to significantly reduce the sintering temperature using nanometer size particles to enhance sintering properties at LT. The strategy is particularly studied in the current development of nanosilver inks at room temperature [5,6]. They have attracted considerable interest as one of the most promising Ag-based conductive materials.…”
Section: mentioning
confidence: 99%
“…Such pastes typically include a solvent, an organic stabilizer and silver particles. The impacts of the nanocrystal size and surface chemistry on the sintering properties have been extensively studied [5,6]. Nanosilver pastes can be sintered at lower temperature compared to bulk silver.…”
Section: Introductionmentioning
confidence: 99%